Controlling the lectin recognition of glycopolymers via distance arrangement of sugar blocks. Issue 1 (6th December 2017) - Jono, K.; Nagao, M.; Oh, T.; Sonoda, S.; Hoshino, Y.; Miura, Y.
Abstract : Control of molecular recognition via living radical polymerization. Abstract : The arrangement of sugars in glycopolymers contributes to their recognition. The molecular recognition of proteins was controlled by the living radical polymerization of glycopolymers. The glycopolymers were prepared by the copolymerization of propargyl methacrylate (Pr-MA) and triethyleneglycol methacrylate (TEG-MA) via living radical polymerization with a reversible addition–fragmentation glycopolymer chain transfer (RAFT) reagent and by subsequent sugar conjugation by click chemistry. The block copolymers were prepared by the polymerization of Pr-MA and TEG-MA. The molecular recognition of glycopolymers was analyzed using the fluorescence quenching of lectin and found to be dependent on the glycopolymer structures. Two-site binding of glycopolymers to concanavalin A (ConA) was attained by both the glycopolymer with a 105-mer and the tri-block glycopolymer with a 103-mer. Glycopolymers with either a 27- or 54-mer showed much weaker interaction because of one-site binding. The molecular recognition of the glycopolymer was controlled by the arrangement and size of the sugar cluster and not by the sugar density.